2020
DOI: 10.1021/acs.jpcb.9b08172
|View full text |Cite
|
Sign up to set email alerts
|

Parametrization and Molecular Dynamics Simulations of Nitrogen Oxyanions and Oxyacids for Applications in Atmospheric and Biomolecular Sciences

Abstract: Nitrogen oxyanions and oxyacids are important agents in atmospheric chemistry and medical biology. Although their chemical behavior in solution is relatively well understood, they may behave very differently at the water/air interface of atmospheric aerosols or at the membrane/water interface of cells. Here, we developed a fully classical model for molecular dynamics simulations of NO3 –, NO2 –, HNO3, and HNO2 in the framework of the GROMOS 53A6 and 54A7 force field versions. The model successfully accounted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…The average coordination number of the nitrite ion in water was calculated. A very recent study by Cordeiro et al 39 presented a systematic development of molecular mechanical models for both nitrate and nitrite ions and their oxyacids and described the solvation and ion-pairing properties through classical simulations. In particular, the model captured experimentally supported properties such as the enrichment of HNO 3 at the water surface and also the surface-induced ion pairing of NaNO 2 .…”
Section: Introduction Aqueous Solutions Of Nitrite (Nomentioning
confidence: 99%
“…The average coordination number of the nitrite ion in water was calculated. A very recent study by Cordeiro et al 39 presented a systematic development of molecular mechanical models for both nitrate and nitrite ions and their oxyacids and described the solvation and ion-pairing properties through classical simulations. In particular, the model captured experimentally supported properties such as the enrichment of HNO 3 at the water surface and also the surface-induced ion pairing of NaNO 2 .…”
Section: Introduction Aqueous Solutions Of Nitrite (Nomentioning
confidence: 99%
“…We carried out MD simulations, in order to study the transport capability of the following RONS from vacuum into the water bulk: H 2 O 2 , HO 2 , OH, O 3 , NO, NO 2 , trans -HNO 2 , cis -HNO 2 , HNO 3 , trans-perp -ONOOH, cis-perp -ONOOH (throughout the main text, tp for trans-perp and cp for cis-perp notations are used) and N 2 O 4 . GROMACS program package (GPU version) [ 41 ] was employed to perform MD simulations by introducing GROMOS united atom force field parameters for RONS developed in the literature [ 42 , 43 , 44 , 45 ]. Initially, the cubic box was filled with an SPC water model [ 46 ] by making use of Packmol software [ 47 ].…”
Section: Simulation Setupmentioning
confidence: 99%
“…Moreover, it is quite complex to mimic a real condition in computer simulations due to the large number of particles in model systems. However, the parameters of the current model system are sufficient to study the permeation process of molecules into the liquid content [ 43 ].…”
Section: Simulation Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters of CER, FFA, and CHO were based on the study of Berger et al [ 39 ] and Höltje et al [ 40 ] The parameters of 5α‐CH were derived from the study reported by Neto and Cordeiro. [ 41 ] The RONS parameters were obtained from the studies reported in References [42–45]. It is noted that HNO 2 has two configurations, that is, trans ‐HONO and cis ‐HONO, and both of them were studied in this study.…”
Section: Computer Simulationsmentioning
confidence: 99%